Pengaruh Pemberian Ekstrak Biji Petai Terhadap Kadar MDA Serum Tikus Yang Diinduksi Pakan Tinggi Lemak - Raihan Afif Salam; Yustini Alioes; Rahmatini Rahmatini (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Background: Petai seed extract (Parkia speciosa Hassk.) contains flavonoids and polyphenols. These compounds have good antioxidant activity to lower oxidative stress. The product of oxidative stress is called MDA (Malondialdehyde) which can be used as an indicator of oxidative stress. The study aimed to determine the effect of petai seeds on MDA serum levels in rats (Rattus novergicus) on a high-fat diet. Objective: To determine the effect of the administration of Methods: This research was a true experimental study with post test only control group design. A total of 25 rats were divided into five groups : negative control (K-), positive control (K+), treatment 1 (P1), treatment 2 (P2), and treatment 3 (P3). The K+, P1, P2, and P3 groups were given a high-fat diet for 30 days and continued to administer extract of petai seeds doses of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW consecutively for P1, P2, P3 for 10 days. The levels of MDA serum were measured by the P. P. Nair method. Data were analyzed using the nonparametric Kruskal-Wallis test and Post-Hoc Mann-Whitney test.Results: The results of this study indicate the effect of the administration of petai seeds (Parkia speciosa Hassk.) on the MDA serum levels. Conclusion: The study concludes that extract of petai seeds with 100 mg/kgBW has no effect on MDA serum levels, while in rats with a dose of 200 mg/kgBW and 400 mg/kgBW can decrease MDA serum levels.